Wear resistance of nickel-titanium endodontic files after surface treatment - Alves-Claro, A. P. R. [UNESP]; Claro, F. A. E. [UNESP]; Uzumaki, E. T. (Springer, 2008)
Objectives The purpose of this work was to submit the Nitinol files to plasma immersion ion implantation (PIII) and evaluate the effects of the surface treatment. Materials and Methods Wear resistance was determined in vitro by using an equipment for the application of horizontal movements on previously prepared notched plates made of resin. Vickers microhardness was measured in plates and files, before and after surface treatment and the surface chemical composition of the instruments was determined by X-rays photoelectron spectroscopy. Results The hardness values found for the treated Nitinol files were significantly lower than the hardness values measured before the implantation process. The comparison of commercially available instruments shows that the wear resistance of the stainless steel file is higher than the resistance of the Nitinol. Conclusions The results found led to the conclusion that the surface treatment significantly increased the Nitinol files wear resistance.